GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SD NEGERI KINTELAN 2 YOGYAKARTA - Eri Susanto; Wasifatun Najiroh; Fina Raudlatul Jannah (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2021)
This research aims to analyze and study the principal's leadership style in improving teacher performance at SD Negeri Kintelan 2 Yogyakarta. This research is qualitative descriptive research. Data collection methods used are observation and interviews. The result of this research is that the principal at SD Negeri Kintelan 2 Yogyakarta has a very good and collective leadership style. The principal at SD Negeri Kintelan 2 has a democratic leadership style, can embrace educators and employees in improving teacher performance, learning quality, and good learning quality quickly, and understands constantly evaluating and correcting deficiencies at SD Negeri Kintelan 2 Yogyakarta with appropriate strategies and methods. fit. To be a good leader, there must be factors that influence the attitude of a leader, including; factors of knowledge or leadership skills, environment, behavior or personality, and social. To become a leader who has good qualities, a school principal must have leadership skills, harmonious ties and cooperation, and a good environment.